RGD-modified injectable hydrogel maintains islet beta-cell survival and function - Tianshu Lan; Jingyi Guo; Xiaoming Bai; Zengjiong Huang; Zhimin Wei; Guicheng Du; Guoliang Yan; Lebin Weng; Xue Yi (Journal of Applied Biomaterials & Functional Materials, 2020)
Objective: A potential solution for islet transplantation and drug discovery vis-à-vis treating diabetes is the production of functional islets in a three-dimensional extracellular matrix. Although several scaffold materials have been reported as viable candidates, a clinically applicable one that is injectable and can maintain long-term functionality and survival of islet pancreatic beta-cells (β-cells) is far from being established. Results: In the current study, we evaluated a ready-to-use and injectable hydrogel’s impact on β-cells’ function and viability, both in vitro and in vivo. We found that β-cells in high concentration with hydrogels functionalized via Arg-Gly-Asp (RGD) demonstrated better viability and insulin secretory capacity in vitro. Moreover, it is a biocompatible hydrogel that can maintain β-cell proliferation and vascularization without stimulating inflammation after subcutaneous injection. Meanwhile, modifying the hydrogel with RGD can maintain β-cells’ secretion of insulin, regulating the blood glucose levels of mice with streptozotocin-induced diabetes. Conclusions: Thus, these preliminary results indicate that this RGD-modified hydrogel is a potential extracellular matrix for islet transplantation at extrahepatic sites, and they also provide a reference for future tissue engineering study.